2019
DOI: 10.1002/ijc.32076
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive metastasis prognosis from plasma metabolites in stage II colorectal cancer patients: The DACHS study

Abstract: Metastasis is the main cause of death from colorectal cancer (CRC). About 20% of stage II CRC patients develop metastasis during the course of disease. We performed metabolic profiling of plasma samples from non‐metastasized and metachronously metastasized stage II CRC patients to assess the potential of plasma metabolites to serve as biomarkers for stratification of stage II CRC patients according to metastasis risk. We compared the metabolic profiles of plasma samples prospectively obtained prior to metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Even if a metabolite was reported in more than one study, often the direction association was different [ 23 ]. For instance, there were no lipid metabolites commonly detected in the same direction in recent studies [ 26 , 28 , 29 ]. The most consistently observed in the same direction as well as by more than one platform were pyruvic acid (up-regulated) and tryptophan (down-regulated) [ 23 ].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Even if a metabolite was reported in more than one study, often the direction association was different [ 23 ]. For instance, there were no lipid metabolites commonly detected in the same direction in recent studies [ 26 , 28 , 29 ]. The most consistently observed in the same direction as well as by more than one platform were pyruvic acid (up-regulated) and tryptophan (down-regulated) [ 23 ].…”
Section: Discussionmentioning
confidence: 91%
“…In the past several years, a number of global metabolomic studies on CRC have been published. These studies utilized diverse biological specimens, including blood (plasma/serum) as the most common type [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], followed by tissue [ 27 , 39 , 40 , 41 , 42 ], feces [ 39 , 40 , 43 ], and urine [ 44 , 45 ], while others aimed specifically to detect volatile metabolites in breath and in other types of biospecimens [ 21 , 46 ]. To our knowledge, only two of these were prospective studies where biospecimens were collected before cancer development [ 26 , 34 ], aiming to identify etiological pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk stratification using non‐invasive parameters has been widely applied in various tumor types for its efficient information provided in clinical decision making. A pretreatment plasma metabolite‐based risk stratification for metastasis in stage II colorectal cancer prognosticated metastasis and non‐metastasis, which provided important information for individualized treatment 40 . Similarly, a smaller sample study combined clinical characteristics and serum protein signatures showed satisfactory synergetic predictive value to group high‐risk and low‐risk patients with pancreatic intraductal papillary mucinous neoplasms 41 .…”
Section: Discussionmentioning
confidence: 96%
“…However, the long-term survival of HCC has not been significantly enhanced [4]. The high recurrence and metastasis rates seriously affect the surgical efficacy and survival of patients, which is an important factor causing poor prognosis of surgical treatment [5,6]. Therefore, effective prediction of the prognostic risk of surgical treatment is particularly important and in urgent need for guiding clinical decisions and Chengnan Fang and Benzhe Su contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%